El adjetivo calificativo Español y su posición dentro del sintagma nominal - Pawlik, Janusz (Studia Romanica Posnaniensia, 2001)
With this little paper we intend to draw the attention of Polish speakers of Spanish to the problem of word order of qualifying adjectives in a noun phrase. In our opinion, this grammatical issue should be tackled successfully only by carrying out an in-depth semantic study of the contents of these noun determiners. For this purpose we are putting forward a general semantic classification of this category of words demonstrating that the meaning of a given item is closely connected with its syntactic position